The functional molecular mass of the Pasteurella hyaluronan synthase is a monomer - Pummill, Philip E.; Kane, Tasha A.; Kempner, Ellis S.; DeAngelis, Paul L. (Biochimica et biophysica acta, 2007)
Hyaluronan (HA), a linear polysaccharide composed of β1,3-GlcNAc-β1,4-GlcUA repeats, is found in the extracellular matrix of vertebrate tissues as well as the capsule of several pathogenic bacteria. All known HA synthases (HASs) are dual-action glycosyltransferases that catalyze the addition of two different sugars from UDP-linked precursors to the growing HA chain. The bacterial hyaluronan synthase, PmHAS from Gram-negative Pasteurella multocida, is a 972-residue membrane-associated protein. Previously, the Gram-positive Streptococcus pyogenes enzyme, SpHAS (419 residues), and the vertebrate enzyme, XlHAS1 (588 residues), were found to function as monomers of protein, but the PmHAS is not similar at the protein sequence level and has quite different enzymological properties. We have utilized radiation inactivation to measure the target size of recombinant full-length and truncated PmHAS. The target size of HAS activity was confirmed using internal enzyme standards of known molecular weight. We found that the Pasteurella HA synthase protein functions catalytically as a monomer. Functional truncated soluble PmHAS also behaves as a polypeptide monomer as assessed by gel filtration chromatography and light scattering.